Trichomoniasis refractory to 5-nitroimidazole therapy in Trinidad. (January 2023) - Edwards, Robert Jeffrey; Parboo, Miriam; Edwards, Jonathan; Boyce, Gregory
Trichomoniasis is the most common non-viral sexually transmitted infection (STI) occurring worldwide and the majority of infected persons (70–85%) have mild or no genital symptoms. Symptoms in women may include a vaginal discharge which may be associated with vulval irritation and most infections can be effectively treated with metronidazole 500mg bd for seven days. Trichomoniasis unresponsive to 5-nitroimidazole therapy is uncommon but results in substantial therapeutic challenges, especially in resource limited countries. We present such a case which was eventually treated with a low-cost intravaginal combination of boric acid and clotrimazole cream.